Predictors of Nonuse of a High‐Potency Statin After an Acute Coronary Syndrome: Insights From the Stabilization of Plaques Using Darapladib‐Thrombolysis in Myocardial Infarction 52 (SOLID‐TIMI 52) Trial. Issue 1 (January 2017) - Eisen, Alon; Cannon, Christopher P.; Braunwald, Eugene; Steen, Dylan L.; Zhou, Jing; Goodrich, Erica L.; Im, KyungAh; Dalby, Anthony J.; Spinar, Jindrich; Daga, Shruti; Lukas, Mary Ann; O'Donoghue, Michelle L.
Abstract : Background: High‐potency statins reduce cardiovascular events after acute coronary syndromes but remain underused in clinical practice. We examined predictors of nonuse of high‐potency statins after acute coronary syndromes. Methods and Results: The Stabilization of pLaques usIng Darapladib‐Thrombolysis in Myocardial Infarction (SOLID‐TIMI 52) trial enrolled patients after an acute coronary syndrome in 36 countries between 2009 and 2011. Statin use was strongly encouraged throughout the trial, and statin potency was at the discretion of the treating physician. A high‐potency statin was defined as ≥40 mg atorvastatin, ≥20 mg rosuvastatin, or 80 mg simvastatin daily. Predictors of nonuse of high‐potency statins were examined using logistic regression. Of the patients included (n=12 446), 11 850 (95.2%) were treated with a statin at baseline after acute coronary syndrome (median 14 days), but only 5212 (41.9%) were on a high‐potency statin. Selected patient factors associated with nonuse of high‐potency statins included age ≥75 years (odds ratio 1.39, 95% CI 1.24–1.56), female sex (odds ratio 1.11, 95% CI 1.02–1.22), renal dysfunction (odds ratio 1.17, 95% CI 1.03–1.32), and heart failure during hospital admission (odds ratio 1.43, 95% CI 1.27–1.62). At 3 months after baseline, only 49% of patients had low‐density lipoprotein cholesterol <70 mg/dL. Among the 5490 patients (59%) who were not on a high‐potency statin at 3 months, lower low‐density lipoprotein cholesterol was a predictor of nonuse of a high‐potency statin after a median of 2.3 years (odds ratio 1.15 for 10 mg/dL decrease, 95% CI 1.11–1.19). Conclusion: Despite the widespread use of statins after acute coronary syndromes, most patients are not treated with high‐potency statins early and late after the event, including patients at the highest risk of recurrent cardiovascular events. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01000727.